Ultrasonic P-Wave to Acquire Parameters of Boise Sandstone - Guangquan Li; Kui Liu; Xiang Li (Geofluids)
Boise sandstone has a variety of grain diameter, and the heterogeneity makes it difficult to characterize. In this paper, a model of viscous squirt is used to simulate velocity and attenuation of ultrasonic P-wave in the sandstone saturated with water. Phase velocity yielding from the model is fitted against the velocity measured at frequency of 500 kHz, which determinates the quality factor due to viscous squirt (Qps) as a function of frequency. The resulting Qps appears to be 14.64 at frequency of 0.8 MHz. With the use of the measured total quality factor (Qp) of 6.9 at 0.8 MHz, the dry quality factor (Qpd) appears to be 13.0 at 0.8 MHz. The resulting dimension of the rock unit is 0.150 multiplied by 0.140 mm, pretty consistent with the mean grain diameter of 0.150 mm. The relative first and second porosities are ascertained to be 0.976 and 0.024, respectively, and the aperture distance of the second porosity is 0.84 μm. Nonetheless, the model represents analytical continuation of small rock samples. Consequently, seismic attenuation predicted by the model is far smaller than field observation. The discrepancy shows that strong seismic attenuation in the field is associated with a scale much larger than pore scale.